Evaluation of hybrid membrane bioreactor (MBR) for palm oil mill effluent (POME) treatment - Ahmad, Zulkifli (Penerbit Universiti Tun Hussein Onn Malaysia, 2011)
The pollution load of palm oil mill effluent (POME) is in the range of 50,000 mg COD/L. With more than 500 palm oil mills, Malaysia produces some 13.9 million tonnes of crude palm oil annually and generates around 35 x 106 m3 POME. Typically, raw POME is difficult to degrade because it contains significant amounts of oil (tryacylglycerols) and degradative products such as di-and monoacylglycerols and fatty acids. The fatty acids composition (C12 – C20) of each of this fraction are different from one another and contribute to the high value of pollution load in POME. Thus POME has to be treated, usually in a series of anaerobic and aerobic treatment steps, for the organic matter to be degraded before the effluent is allowed to be discharged into public waterways. The objective of this study was to observe the performance of a hybrid membrane bioreactor (MBR) for POME. The raw POME was introduced into sequencing processes of anaerobic, anoxic and aerobic in order to achieve biological nutrient removal and the membrane modules were submerged into the aerobic zone. The critical flux of MBR using the flux-step method based on transmembrane pressure (TMP) was conducted as well as flux and permeability studies for assessing fouling in a membrane bioreactor operating at constant flux. The reactor was operated at a mixed liquor suspended solid (MLSS) concentration of 4000 to 8000 mg/l. The removal efficiency of COD, SS, TN and TP achieved were 94%, 98%, 83% and 64% respectively. The hybrid MBR was found to be able to degrade POME significantly and high quality effluent could be reused for various other applications.